Kobiecość i metafizyka w filmach Jeana-Claude'a Brisseau = Feminity and metaphysics in Jean-Claude Briesseau's films - Prusinowski, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
French director Jean-Claude Brisseau (1944-2019) started his career as a social realist. Over time, he gradually abandoned his harsh semidocumentary approach to filmmaking and adopted a more visually refined style. The imagery in his films reflected metaphysical and often esoteric contents.
Keywords: kino francuskie; metafizyka; surrealizm; French cinema; metaphysics; surrealism